Wellbeing of Indigenous Peoples in Canada, Aotearoa (New Zealand) and the United States: A Systematic Review - Alana Gall; Kate Anderson; Kirsten Howard; Abbey Diaz; Alexandra King; Esther Willing; Michele Connolly; Daniel Lindsay; Gail Garvey (International Journal of Environmental Research and Public Health, 2021)
Despite the health improvements afforded to non-Indigenous peoples in Canada, Aotearoa (New Zealand) and the United States, the Indigenous peoples in these countries continue to endure disproportionately high rates of mortality and morbidity. Indigenous peoples’ concepts and understanding of health and wellbeing are holistic; however, due to their diverse social, political, cultural, environmental and economic contexts within and across countries, wellbeing is not experienced uniformly across all Indigenous populations. We aim to identify aspects of wellbeing important to the Indigenous people in Canada, Aotearoa and the United States. We searched CINAHL, Embase, PsycINFO and PubMed databases for papers that included key Indigenous and wellbeing search terms from database inception to April 2020. Papers that included a focus on Indigenous adults residing in Canada, Aotearoa and the United States, and that included empirical qualitative data that described at least one aspect of wellbeing were eligible. Data were analysed using the stages of thematic development recommended by Thomas and Harden for thematic synthesis of qualitative research. Our search resulted in 2669 papers being screened for eligibility. Following full-text screening, 100 papers were deemed eligible for inclusion (Aotearoa (New Zealand) n = 16, Canada n = 43, United States n = 41). Themes varied across countries; however, identity, connection, balance and self-determination were common aspects of wellbeing. Having this broader understanding of wellbeing across these cultures can inform decisions made about public health actions and resources.